2010
DOI: 10.1021/am900682s
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Thermoplastic Polyimide with Dispersed Functionalized Single Wall Carbon Nanotubes

Abstract: Molecular pi-complexes were formed from pristine HiPCO single- wall carbon nanotubes (SWCNTs) and 1-pyrene- N-(4-N'-(5-norbornene-2,3-dicarboxyimido)phenyl butanamide, 1. Polyimide films were prepared with these complexes as well as uncomplexed SWCNTs and the effects of nanoadditive addition on mechanical, thermal, and electrical properties of these films were evaluated. Although these properties were enhanced by both nanoadditives, larger increases in tensile strength and thermal and electrical conductivities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 72 publications
3
35
1
Order By: Relevance
“…Potential applications of CNT yarns that possess both good electrical and mechanical properties include antennas and lightning strike protection of aircraft [7]. Considerable efforts have been focused until now in e-beam irradiation methods that lead to mechanical improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications of CNT yarns that possess both good electrical and mechanical properties include antennas and lightning strike protection of aircraft [7]. Considerable efforts have been focused until now in e-beam irradiation methods that lead to mechanical improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNT) have been shown to improve the properties of polymers such as structural and thermal properties (Lebron-Colon et al, 2010). In order to investigate the effects of CNT addition on high temperature Synthesis and characterization of polyimide-carbon nanotube composites polyimides, nanocomposites were prepared with 0 and 1 wt% CNTs (functionalized and nonfunctionalized Single-and Double-Wall).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, considerable attention has been paid to the modification of PI film with organic/inorganic hybrid materials. It was found that the electrical, mechanical, thermal properties of PI films were significantly improved by the doping of a small amount of nano-fillers [2,3].…”
Section: Introductionmentioning
confidence: 99%